STRATEGIC PLANNING IN THE MANAGEMENT OF DEVELOPMENT OF HOUSE-BUILDING ENTERPRISES - R. A. Kadyrov; R. M. Dullueva (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
The system of the shaping strategic plan developments house-building enterprises is offered in sloppy condition market. The considered problems and methodical bases of the shaping adaptive strategic plan and tree of the sub goal to main strategic purpose of the development house-buildingenterprises.